العلاج الجراحي لكسور فوق اللقمتين عند الأطفال ( نتائج وظيفية ) - سعد, معن; المحمد, عزت; حاج إسماعيل, مهند (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في قسم الجراحة- مشفى الأسد الجامعي- اللاذقية– سورية، حيث شملت 37 مريضاً, 25 ذكراً (67%) و12 أنثى (33%). عولج الجميع جراحياً. لم نصادف مضاعفات قبل الجراحة. حدثت لدينا إصابة عصب زندي علاجية المنشأ, وتراجعت بعد أربعة أشهر. عشر مرضى (27%) حدثت لديهم مضاعفات على المدى البعيد ( إنتان, فحج, .... ). This study, which was conducted at al-Assad Hospital, Lattakia, Syria, included 37 patients "25 males" (67%) and "12 females" (33%): We treated all of them by surgical treatment. We have not noticed any complications before the surgery. We had iatrogenic ulnar nerve injury, but it had completely resolved in 4months. 10 patients (27%) happened to have complications after a long time (track infection, varus ……).